(untitled) (International Journal of Innovative Technologies in Economy, 2025)
This study addresses the issue of poor financial record-keeping practices among micro, small and medium enterprises (MSMEs) in Palintang Hamlet, most of which are engaged in agriculture and the sale of local products such as coffee and vegetables. The lack of record-keeping leads to ineffective financial management, difficulties in identifying profits or losses, and challenges in managing business capital (Putri & Nurlaila, 2022; Maris et al., 2022; Thadeus, Simiyu, & Ombaba, 2023). This study aims to enhance understanding of simple financial record-keeping through socialisation activities conducted as part of the Thematic Community Service Learning (TCSL) programme. The method used was pre-experimental with pre-test and post-test instruments to measure participants’ understanding improvement. The analysis results showed a significant increase in participants’ understanding after the socialisation, evidenced by a statistically significant difference in the average pre-test and post-test scores (Asymp. Sig. 0.046 < 0.05), with 9 out of 17 participants experiencing an increase in scores. The conclusion of this study is that the socialisation of simple financial record-keeping can effectively improve the financial literacy of SME actors, which serves as an important foundation for capital management and business sustainability in Palintang Village.